Implementasi Metode Pembiasaan Keagamaan dalam Membentuk Karakter Religius Siswa di SMK Ma’arif 6 Ayah - Rosuli, Abdi; Hasyim, Fuad (IAINU Kebumen, 2024)
The research objectives are: (1) to analyze the implementation of the religious habituation method in forming the religious character of students at SMK Ma'arif 6 Ayah; (2) to analyze the supporting and inhibiting factors for the implementation of religious habituation methods in forming students' religious character at SMK Ma'arif 6 Ayah. The method used by researchers is qualitative with data collection techniques including interviews, observation and documentation. The sample in this research was class X TAV 1 students at Ma'arif 6 Ayah Vocational School for the 2023/2024 academic year. The results of research regarding the implementation of religious habituation methods in forming the religious character of students at Ma'arif 6 Ayah Vocational School are: (1) Getting used to reading Surah Al-Waqiah; (2) Getting used to reading Surah Al-Mulk; (3) Getting used to reading Surah Ar-Rahman, (4) Getting used to Yasin, Tahlil, and Infaq; (5) Getting used to reading Asmaul Husna; (6) Getting used to Dhuha prayers in congregation; (7) Getting used to Dhuhr prayers in congregation. This habituation activity is carried out during the first hour of learning, namely 07.00 WIB until finished. The character values ​​instilled in students include honesty, responsibility, caring for the environment, discipline and religion. The supporting factors in implementing the religious habituation method in forming the religious character of students at Ma'arif 6 Ayah Vocational School are : (1) Adequate facilities; (2) Adequate facilities and infrastructure; (3) Students are disciplined in participating in habituation activities; and (4) The role of first hour teachers in guiding students in class; (5) Adequate PAI teacher human resources. Meanwhile, the inhibiting factors are (1) There are still many students who cannot read the Qur'an; (2) Many students feel unfamiliar with the Dhuha Prayer; (3) The students' backgrounds are different; (4) Non-religious environment; (5) Lack of Student Awareness